2023
DOI: 10.1002/aic.18298
|View full text |Cite
|
Sign up to set email alerts
|

Ionization‐engineered two‐dimensional confined channels in GO membranes for highly efficient OH separation

Yong Li,
Rui Jia,
Ruonan Tan
et al.

Abstract: OH− sieving membranes provide a valuable means for treating alkaline effluents but their development presents several challenges. In this study, the concept of ionization engineering is applied to two‐dimensional (2D) laminated membranes to facilitate OH− separation. This concept is demonstrated through the stacking of the self‐designed sulfonated graphene oxide (SGO) nanosheets to fabricate 2D membranes. The SGO membranes enhance synergistically the OH− dialysis coefficients and separation factors when treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The UOH and SOH/WO42 of SPX membranes with varied thicknesses were in the range of 2.34 × 10 −3 –9.74 × 10 −3 m h −1 and 346–649, respectively. A comparison made on UOH and SOH/WO42 with reported membranes, as shown in Figure 5C, SPPO‐based membranes, 49–51 PVA‐based membranes, 24 two‐dimensional sulfonated graphene oxide membranes, 52 and other hybrid membranes, 24,53–57 showed that the microporous SPX membrane balanced well with the OH − dialysis coefficient and OH − /WO 4 2− selectivity. For instance, the PVA‐MIDA hybrid membrane exhibited a very high OH − dialysis coefficient of 0.022 m h −1 but a low OH − /WO 4 2− selectivity of 33 54 .…”
Section: Resultsmentioning
confidence: 90%
“…The UOH and SOH/WO42 of SPX membranes with varied thicknesses were in the range of 2.34 × 10 −3 –9.74 × 10 −3 m h −1 and 346–649, respectively. A comparison made on UOH and SOH/WO42 with reported membranes, as shown in Figure 5C, SPPO‐based membranes, 49–51 PVA‐based membranes, 24 two‐dimensional sulfonated graphene oxide membranes, 52 and other hybrid membranes, 24,53–57 showed that the microporous SPX membrane balanced well with the OH − dialysis coefficient and OH − /WO 4 2− selectivity. For instance, the PVA‐MIDA hybrid membrane exhibited a very high OH − dialysis coefficient of 0.022 m h −1 but a low OH − /WO 4 2− selectivity of 33 54 .…”
Section: Resultsmentioning
confidence: 90%